A Culturally Relevant Care Model to Reduce Health Disparities Among Medicaid Recipients. (March 2022) - Johnson, Andrew; Murcko, Anita; Castro Thompson, Anabell; Merica, Chandra; Stephan, Mark
Health disparities among Hispanics are associated with poorer health status across multiple health conditions, greater use of high-acuity services, and lower use of care continuity and preventive services. A new integrated delivery organization (IDO) designed around culturally responsive care aims to reduce health disparities and improve health outcomes among the Hispanic community by deploying a multifeatured approach. The IDO combines the universal administration of a culturally sensitive health risk screening tool, the delivery of culturally appropriate medical, behavioral and spiritual health, and creative support of provider practices with training and informational resources, financial incentives, actionable data, technology, and cultural sensitivity training for providers and staff. The IDO further distinguishes its unique approach by partnering with a university informatics program to establish a local learning health care system destined to enrich the evidence base for culturally appropriate interventions that reduce health disparities. Longitudinal research is currently underway that focuses on the impact of culturally motivated interventions on resource utilization, retention, and quality.